Analisis Faktor yang Mempengaruhi Kejadian Infeksi Nosokomial Flebitis di Rumah Sakit Umum Daerah Kabupaten Muna - Intan Eskawati Ahmad; Syamsul Rijal; Haryati Haryati (Jurnal Surya Medika (JSM), 2020)
Phlebitis is one of the nosocomial infections related to invasive procedures. One of the most common invasive procedures in hospitals is infusion therapy. Phlebitis can cause thrombosis, which if continued, can lead to death. Purpose: The aims of this study were to determine the factors that affect the incidence of phlebitis nosocomial infection in the general hospital of Muna regency. The study design was using quantitative research with a cross-sectional study. The sample of this study was 60 inpatients who got infusion therapy and met the inclusion criteria. The sampling technique was using Proportional Random Sampling. Data were collected by direct observation method and data analysis was using a chi-square statistical test with a confident interval of 95% (alpha = 0.05). The median age of respondents was 37 (range 20 – 50) years and 31 (51.7%%) of the respondents were females. The respondent that have duration infusion less than or equal to 3 days were 39 (65%), respondent with one type of intravenous fluid was 55 (91.7%), a respondent who received antibiotic or Nonsteroidal Anti-Inflammatory Drugs (NSAID) injection therapy was 38 (63.3%), and as many as 20 (33.3%) respondents experienced phlebitis infection. The bivariate analysis showed that the factors that affect the incidence of phlebitis nosocomial infection were duration of infusion (p-value = 0.000), amount of intravenous fluids (p-value = 0.038), and injection therapy (p-value = 0.014). The duration of infusion, amount of intravenous fluid, and injection therapy affect the incidence of phlebitis nosocomial infection in the general hospital of Muna regency.